Energy and carbon budgeting of tillage for environmentally clean and resilient soil health of rice-maize cropping system. (20th July 2019) - Lal, B.; Gautam, Priyanka; Nayak, A.K.; Panda, B.B.; Bihari, P.; Tripathi, R.; Shahid, M.; Guru, P.K.; Chatterjee, D.; Kumar, U.; Meena, B.P.
Abstract: Human interventions in the environment leading to higher green house gas emissions which are degrading the soil and environment quality. Traditional/conventional tillage systems following since inception and residue burning are accelerating the degradation of soil and environment leading to food insecurity. The present study was executed to evaluate energy budgeting, carbon foot prints, gaseous emission and soil health under conservation tillage with residue retention for identifying cleaner production technology in rice-maize system. The novelty of the study is that it examines the integrated effect of tillage, residue retention through mulching on GHG emission along with soil health, energy consumption and carbon footprints together as conservation effective measure for sustainable and clean agricultural production. Zero tillage reduced the energy consumption by 56% and carbon footprints by 39% and besides that N2 O emission was 20% lower than conventional tillage. Apart from clean environment, soil health was also improved by adoption of zero tillage in terms of NPK status, labile pool of carbon and enzymatic activities; the population of all the microbiota was increased, which was around 21.3, 51.2 and 27.6% higher in bacteria, fungi and actinomycetes. Crop residue retention as residue mulching (rice straw) significantly improved the crop productivity, microbial biota and enzymatic activities of soil, but it increased the energy consumption and carbon footprints by around 10%. N2 O emission was also enhanced by residue mulching, and higher the quantity of residue used as mulch, more was emission. Although in initial years some yield penalty (10–15%) was recorded but in long run zero tillage can be a step towards sustainability as it can be a valuable approach for resilient soil health and cleaner production of maize in rice–maize system. Highlights: Energy, carbon, Soil health and N2 O emission was evaluated in rice-maize under different tillage and mulching. Under zero tillage, energy use efficiency and energy productivity can be increased by 19.2% and 18.1%. N2 O emissions were about 20% lower in zero tillage than conventional tillage in maize. Zero tillage reduced the carbon foot prints by 293 and 11 % in diesel and labour, leading to 39% total reduction. Zero tillage improved the soil health, carbon pool and enzymatic activities but yield penalty of 10–15%.